Working environment-related tension experienced by staff in Greek hyperbaric medicine units - Chandrinou, Angeliki; Exarchos, Konstantinos; Bissias, Christos; Gaitanou, Kostantina; Sarafis, Pavlos; Malliarou, Maria (My University, 2013)
Working conditions in hyperbaric medicine units has not been explored as yet by the international hyperbaric community.
Keywords: Working conditions; Hyperbaric Medicine Units